Floral anatomy of Eriocaulon elichrysoides and Syngonanthus caulescens (Eriocaulaceae) - Rosa, M. M.; Scatena, V. L. (Urban & Fischer Verlag, 2003)
The floral anatomy of Eriocaulon elichrysoides Bong. and Syngonanthus caulescens (Poir.) Ruhland, from Brazilian mountain rock savannas (campos rupestres) was studied. The staminate flowers of E. elichrysoides present a diplostemonous androecium with six stamens, and those of S. caulescens present an isostemonous androecium with three stamens and three scalelike staminodes. Eriocaulon elichrysoides and S. caulescens have three nectariferous pistillodes located in the central portion of the receptacle. The pistillate flowers of E. elichrysoides present three simple styles while those of S. caulescens present three simple styles interspersed with three nectariferous appendices. Both the styles of E. elichrysoides and the nectariferous appendices of S. caulescens are vascularized by the dorsal vascular bundles of the carpels. The styles of S. caulescens lack vascularization. At the base of the gynoecium of E. elichrysoides there are six staminodes and there are three in the S. caulescens. Entomophily is suggested as the pollination syndrome in E. elichrysoides and S. caulescens as they present staminate and pistillate flowers with nectariferous structures. The ancestral character in Eriocaulon is probably given by the presence of the two staminal whorls. The staminate flowers of S. caulescens are probably derived from the reduction of a diplostemonous ancestral androecium. It remains open whether the pistillate flowers with nectariferous, appendices present an ancestral character or a derived one.
Keywords: Eriocaulaceae; floral anatomy; Eriocaulon elichrysoides; Syngonanthus caulescens; monocots; pollination biology